2013
DOI: 10.1002/wrcr.20502
|View full text |Cite
|
Sign up to set email alerts
|

The effect of free-phase NAPL on the spectral induced polarization signature of variably saturated soil

Abstract: [1] In this study, the influence of a free phase nonaqueous phase liquid (NAPL), decane, on the soil's SIP signature was experimentally investigated. The complex electrical conductivity was determined using the SIP measurement system and compared between two main treatment types: clean and decane contaminated. Complementary chemical and temporal measurements were conducted. The results show a clear decrease in the imaginary part of the complex conductivity for the decane contaminated soil. Moreover, a shift of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…For example, Shefer et al (2013) presented a conceptual model of these conditions, where the NAPL was, as we understand it, assumed to create rings around air-filled pores by displacement of the water phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Shefer et al (2013) presented a conceptual model of these conditions, where the NAPL was, as we understand it, assumed to create rings around air-filled pores by displacement of the water phase.…”
Section: Discussionmentioning
confidence: 99%
“…In published research, interpretation of IP data often rely on different conceptual models of NAPL configuration, which in different ways explain the observed results (e.g. Olhoeft, 1985;Titov et al, 2004;Martinho et al, 2006;Schmutz et al, 2010;Revil et al, 2011;Flores Orozco et al, 2012;Shefer et al, 2013). However, to date, there are no comparative studies discussing possible effects of different models.…”
Section: Introductionmentioning
confidence: 95%
“…Considerable effort has been devoted to developing noninvasive, geophysical methods for detecting NAPL distributions. These methods have included using time domain reflectometry [Persson and Berndtsson, 2002], measuring self-potential signals [Minsley et al, 2007], using nuclear magnetic resonance measurements [Bryar and Knight, 2008], and applying the spectral induced polarization technique Shefer et al [2013]. Revil and Mahardika [2013] demonstrated that seismoelectric effects could be used to identify the position of a NAPL-water encroachment front.…”
Section: Field Studies Of Napl Flow and Entrapmentmentioning
confidence: 99%
“…; Kemna et al . ; Shefer, Schwartz, and Furman ). In addition, several authors have studied the influence of fluid saturation on complex impedance (Vinegar and Waxman ; Ulrich and Slater ; Titov et al .…”
Section: Introductionmentioning
confidence: 99%
“…Using equivalent circuit theory, the induced polarisation can be related to the coupling between the components of capacitance and resistance. It has been suggested that the physical mechanism of induced polarisation is related to the electrical double layer and membrane polarisation at lower frequencies and the Maxwell-Wagner polarisation at higher frequencies (Chelidze and Gueguen 1999;Chen and Or 2006;Revil and Florsch 2010;Jougnot et al 2010;Kemna et al 2012;Shefer, Schwartz, and Furman 2013). In addition, several authors have studied the influence of fluid saturation on complex impedance (Vinegar and Waxman 1984;Ulrich and Slater 2004;Titov et al 2004;Binley et al 2005;Cassiani et al 2009;Xiao et al 2009;Jougnot et al 2010;Schmutz et al 2010;Kavian, Slob, and Mulder 2012;Schmutz, Blondel, and Revil 2012;Su, Feng, and Shang 2000).…”
mentioning
confidence: 99%